Analysis of the Influence of the Use of Artificial Intelligence (AI) in Academic Interactions on Students' Language Politeness - Purnamasari, Ramdani; Ikhwannul Muslimin (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
The use of Artificial Intelligence (AI) in higher education is increasingly widespread, but its impact on pragmatic competencies such as language politeness has not been widely studied. This study aims to: (1) measure the effect of AI use on students' language politeness, (2) explore students' interpretations of these changes, and (3) analyze significant differences between groups using AI and those not. This study used a mixed method with a quasi-experimental design involving students divided into experimental (n=30) and control (n=29) groups. Data were collected through language politeness tests (pre-test and post-test), Focus Group Discussions (FGD), interviews, and observations, then analyzed statistically (t-test) and thematically. The results showed that: (1) There was a significant increase in the experimental group (from an average of 53.70 to 60.17; p < 0.001). (2) Students perceive AI as a learning partner that triggers cognitive, behavioral, and affective transformation, and (3) There is no significant difference between the scores of the experimental and control groups (p = 0.138). These findings indicate that although AI is effective in improving language politeness, the improvement can be matched by other methods that are also successful in raising metapragmatic awareness. The control group achieved equivalent results through the use of social support (social scaffolding), intensive self-evaluation, and high motivation triggered by awareness as research participants (Hawthorne Effect). Therefore, it can be concluded that metapragmatic awareness is a key factor that is more decisive in improving language politeness, compared to simply using certain tools or technologies.